MINAT BELAJAR SAINS ANAK USIA 5-6 TAHUN DI TK PEMBINA NEGERI I BANGKO - Salmah, Salmah; Indarto, Wusono; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research was done because of the interest in learning scince of children in TK Pembina Negeri 1 Bangko can not be developed to the fullest. The purpose of this research was to determine how the interest in learning science in children aged 5-6 years in TK Pembina Negeri 1 Bangko. Population and sample in this research is all children aged 5-6 years in group B-2, amounting to 17 people. This research uses descriptive method that aims to provide a systematic overview of the situation that took place on the object of research that is interest in learning science in children aged 5-6 years in TK Pembina Negeri 1 Bangko. The result of research showed that the interest in learning science in children aged 5-6 years were on average 77,21 % in the range of 76-100 %, with the criteria of â€œVery Goodâ€.Keywords: Interest In Learning,Science